THE EFFECT OF CASH TURNOVER, CURRENT RATIO, COMPANY SIZE AND SALES GROWTH ON RETAIL TRADE PROFITABILITY - Sherly -; Marcella Jocelyn Wijaya; Valeriana Sethevani; Tina Novianti Sitanggang (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
The purpose of the study was to find out the relationship between cash turnover, current ratio, company size, and sales growth in retail trade organizations. Retail trading businesses listed on the Indonesia Stock Exchange (IDX) between 2017 and 2020 became the population in the study.This research uses a purposive selection approach, with the criteria for retail trading business actors listed on the Indonesia Stock Exchange to suffer losses and not submit comprehensive financial statements during the period 2017-2020. Quantitative data analysis approaches are used in this research. Some of the tests used in this hypothesis experiment: multiple linear regression, T test, F test, and determination coefficient.The study's findings include The Current Ratio, which statistically has a significant impact on profit margins. Meanwhile, the cash turnover ratio, the size of the company, and the rate of increase in sales did not have a great influence on profitability. However, cash turnover ratios, current ratios, company sizes, and sales growth all have a statistically significant positive impact on profitability when combined.